Early predictors of first-year academic success at university: pre-university effort, pre-university self-efficacy, and pre-university reasons for attending university. Issue 1 (17th February 2017) - van Herpen, Sanne G. A.; Meeuwisse, Marieke; Hofman, W. H. Adriaan; Severiens, Sabine E.; Arends, Lidia R.
ABSTRACT: Given the large number of dropouts in the 1st year at university, it is important to identify early predictors of 1st-year academic success. The present study ( n = 453 first-year students) contributes to literature on the transition from secondary to higher education by investigating how the non-cognitive factors pre-university effort and pre-university academic self-efficacy influence 1st-year retention at university. In addition, we examined pre-university reasons for attending university and whether these reasons were related to 1st-year retention. Multinomial logistic regression analyses showed that pre-university effort positively predicted 1st-year retention, whereas pre-university academic self-efficacy did not. With exploratory factor analysis and confirmatory factor analysis, we identified six pre-university reasons for attending university: career perspective, personal development, compliance with the social environment, attractiveness of the institution, recommended by others, and location. None of the pre-university reasons appeared to significantly predict 1st-year retention. Implications for research and practice are discussed.